Direct Chip Mounting — A Challenge to the Design Engineer. (1982) - Lorman, J.; Prochaska, J.
Abstract : The extrapolation of development trends in the area of technologically complicated electronic equipment shows an ever increasing complexity in semiconductor technology. This development has so concerned the constructors of electronic equipment that progress in the technology of mounting and interconnection has taken a secondary place. This growing divergence between a fast developing microelectronic industry, and a conservative state of the macroelectronics industry, is a driving force with regard to the progress to effective connection technologies at every level of mounting. The technological solution to all systems will then become more coordinated. The mounting of components to printed circuit boards is traditionally a soldering operation. This principle lead to the development of full automation, and is a standard mounting technology. The growth of integration at the chip level has however brought new requirements that are only satisfied with difficulty. Newly developed requirements show that the use of dual-in-line packages will be unsatisfactory. New methods must be designed to connect the chips directly to the printed circuit board, going from the chip as the smallest mounted unit. Requirements for very complex electronic equipment with a high degree of integration (LSI or VLSI) are not satisfied using traditional mounting systems. These require a totally new mounting concept, from the chips to the printed circuit board. In this paper alternatives to printed circuit board technology with insulated wiring (multilayers), and the mounting of chips from film carriers, are evaluated. These principles have a good possibility of further improvement as progress in mounting technology continues. Price reductions cause an extension of application possibilities and an extension of electronic designs. It is harder to make choices for new designs when there are more degrees of freedom. However the function of chips as the basic element is unchangeable and optimum designs need to be based on this concept.